Invasion mechanism of bovine aortic endothelial cells by Pasteurella multocida serotype B:2 - Yap, Seng Kar (2016)
Pasteurella multocida serotype B:2 (Asian strain) is normally found as a commensal in the upper respiratory tract of large ruminants. However, the bacteria are also the causative agent of hemorrhagic septicemia (HS), an economically important disease affecting cattle and buffaloes. In addition, outbreaks of HS are still commonly reported among vaccinated cattle and buffaloes which often associated with poor vaccine-induced immunity. Hence, there is a need to characterize the pathogenic mechanism of P. multocida serotype B:2 (PM B:2) in order to understand the pathogenic factors that associated with the bacterial attachment, entry and invasion of cells following infection. This study aims to investigate the effects of immunomodulatory molecules namely dexamethasone (DEXA) and lipopolysaccharide (LPS) treatment on PM B:2 invasions of bovine aortic endothelial cells (BAECs). In vitro invasion assay was performed to determine the invasive capability of the bacteria toward treated and untreated BAECs by using viable plate count and quantitative real-time polymerase chain reaction (qPCR). Immunofluorescence microscopy and transmission electron microscopy (TEM) were used to detect the internalized bacteria in BAECs. Meanwhile, actin filament particularly F-actin and G-actin of treated and untreated BAECs were examined and quantified by using fluorescence microscopy. The results showed that treatment of BAECs with LPS at 50 and 100 ng/mL for 24 h increased the number of intracellular bacteria per cell (CFU/cell) (p<0.05) compared with DEXA-treated and untreated cells. No significant differences were detected in the number of intracellular bacteria from DEXA-treated cells and the untreated control cells. In addition, the findings of this study also showed that the fluorescence units per area of F-actin pool were decreased which associated with the increased in G-actin pools following treatment of BAECs with LPS at 100 ng/mL for 24 h. The changes of the F-actin and G-actin pools indicate of actin filament depolymerization of the cells. As expected such changes were not detected from control BAECs and BAECs treated with 10 μM DEXA for 24 h. This study also found differences in the location of the bacteria in BAECs. Based on the TEM results, the bacteria were found in the vacuoles of the DEXA-treated cells and untreated cells, whereas the bacteria internalized within the plasma membrane of the LPS-treated cells probably due to the effect of LPS on the actin filaments. In conclusion, this study suggests that treatment of LPS affects the actin filaments of BAECs which could facilitate the invasion of PM B:2 into endothelial cells. Further study is required in order to identify the virulence factors of PM B:2 that associated intracellular invasion.